Peningkatan Pengetahuan Masyarakat tentang Fluor dalam Pencegahan Karies Gigi di Gampong Lamraya Aceh Besar - Mufizarni; Mardelita, Sisca; Keumala, Cut Ratna; Reca, Reca; Ratna Willis (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Dental caries are damage to tooth tissue starting from tooth enamel to spreading to dentin. To maintain this hardness, the enamel is in dire need of a chemical ion called fluorine. Lack of fluor can also cause tooth decay. In this community service, the community's knowledge about fluoride was increased to prevent dental caries by using the Lecture, Question and Answer, Demonstration, Discussion, and Simulation methods. Based on the results of community service that has been carried out, it can be concluded that there is an increase in public knowledge about fluor in preventing dental caries in the Lamraya Aceh Besar village community. It is recommended that people always maintain dental health and consume lots of foods and drinks that contain fluoride.  Keywords: Fluor, Knowledge